Enxerto ou implante homólogo na correção de defeito ósseo segmentar femoral em cães associado a inoculação da fração de células mononucleares da medula óssea - Salbego, Fabiano Zanini (2010)
Bone defects due to trauma, postoperative and mutilating surgery complications, associated to removal of neoplasia, are part of the routine of hospitals and veterinary clinics. Bone grafts, within all their variants, represent the main viable alternative in the structural correction of great bone losses. Currently, the search for alternatives to correct these problems and the great potential of cellular therapy, have led numerous researchers to ingress into this line of study. The present work aimed to evaluate the influence of the hydration of bone implants conserved in glycerin 98% over their biomechanical resistance; the viability of a bone marrow harvesting protocol, for application in the clinical surgical routine; and the effect of intralesional application of bone marrow mononuclear cell fraction, over the consolidation of graft-host interface of dogs submitted to segmental bone grafting, with bone implants conserved in glycerin 98%. This research was developed in two phases. The first, ex-vivo, in which 108 bone fragments conserved in glycerin 98% were separated in six different groups, according to hydration period, and later were submitted to axial load test for biomechanical resistance evaluation. The second phase, in-vivo, in which 20 mongrel dogs, with mean weight of 13kg, were divided in four different groups according to the type of graft employed and with or without application of bone marrow mononuclear cell fraction. All animals were submitted to a bone marrow harvesting protocol, obtaining a final volume of 5ml kg-1 of body weight. The collected bone marrow was analyzed by means of myelogram and later submitted to isolation of the mononuclear cell fraction by a technique already affirmed in the literature. A diaphyseal femoral bone defect was created and repaired with the same removed segment (groups I and III) or with a bone segment conserved in glycerin 98% (groups II and IV). The bone marrow mononuclear cell fraction, after isolation, was injected via intralesional route in dogs of the treated groups (I and II), whereas the control group (III and IV) received an injection of the same volume, however, of 0.9% sodium chloride solution. The bone consolidation progress of the graft-host interfaces was followed by serial radiographic exams up to 90 days after surgical intervention, whereas the presence of mononuclear cells was followed up to seven days after implantation, by detection of Qtracker-665 nanocrystal fluorescence, used as cell marker. According to the results obtained, it can be concluded that: hydration of bone implant conserved in glycerin 98% does not produce statistically significant alterations in the biomechanical resistance of cortical bone for the different evaluated times. However, the bone mineral density has a close relationship with this property; bone marrow harvesting protocol with reduced volume of 5ml kg-1 of body weight, obtained from different long bones, proved to be adequate for isolation of mononuclear cell fraction and for obtaining a cell button with adequate number of cells and high viability, essential for the success of its therapeutic application; the consolidation of proximal and distal graft-host interfaces at 90 days after surgery no showed clinical and radiographic difference in the groups control and treated with bone marrow mononuclear cell fraction. Nevertheless, it cannot be confirmed that the cellular therapy used in this study is not an effective bone healing adjuvant, as it is believed that the restriction of load deposition on the focus of the fracture, achieved by reduced postoperative exercise, has influenced directly on the result of the consolidation.